2010
DOI: 10.1111/j.1532-950x.2009.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

A Technique for Laser-Facilitated Equine Pastern Arthrodesis Using Parallel Screws Inserted in Lag Fashion

Abstract: In horses with advanced PIJ OA, this technique appears to be a viable alternative for PIJ arthrodesis. Further study including characterization of the effects of the laser, ideal case selection indications, and optimal laser dose is indicated before this technique is recommended for routine PIJ arthrodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…However, the goal of surgery in our case (i.e., bilateral subluxation) was to achieve a more equal load distribution among hind limbs and to institute early normal motion. Other reliable techniques for the treatment of DS-PIJ include arthrodesis [5,6,13,14], screw fixation, and dynamic compression plates associated with ankylosis of the PIJ [1,12,16,17]. However, surgical procedures should be chosen by the practitioner on a caseby-case basis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the goal of surgery in our case (i.e., bilateral subluxation) was to achieve a more equal load distribution among hind limbs and to institute early normal motion. Other reliable techniques for the treatment of DS-PIJ include arthrodesis [5,6,13,14], screw fixation, and dynamic compression plates associated with ankylosis of the PIJ [1,12,16,17]. However, surgical procedures should be chosen by the practitioner on a caseby-case basis.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term convalescence (up to 6 months) and excessive care are necessary in order to avoid instability of the PIJ in these cases [3]. Direct surgical techniques, such as arthrodesis [6,[12][13][14], screw fixation, and dynamic compression plates associated with chemical or physical ankylosis also have been successfully used to correct the PIJ angle of the hind limb in cases of subluxation [2,12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Watts and colleagues also performed the surgery with the horse under general anaesthesia and used a diode laser to destroy articular cartilage followed by three transarticular screws. 19 These authors reported that all horses were able to return to their previous use by 12 months.…”
Section: Introductionmentioning
confidence: 98%
“…13,[16][17][18] Minimally invasive techniques to arthrodese the proximal interphalangeal joint have been described. 1,19 Jones and colleagues performed minimally invasive surgery under general anaesthesia and utilized placement of a dorsal plate using a limited surgical approach, avoiding tendon and ligament transection and without complete articular cartilage removal. These authors reported that 8/11 horses were able to meet owners' expectations after surgery.…”
Section: Introductionmentioning
confidence: 99%